Colchicine use might be associated with lower mortality in COVID‐19 patients: A meta‐analysis - Mohamed Nabil Elshafei (9960500) (2023)
Background Colchicine was recently repurposed for the management of coronavirus disease 2019 (COVID-19). This rapid review and meta-analysis aimed to assess colchicine's impact on mortality outcomes in COVID-19 patients. Materials and Methods We systematically searched PubMed, EMBASE, Google Scholar since their inception till 25/03/2021 for observational or controlled studies that reported mortality as an outcome. The mortality odd ratios were generated with their corresponding 95% confidence intervals utilizing the random-effects model. Results Nine studies comprising 5522 patients met our inclusion criteria. Our meta-analysis revealed significantly lower mortality in the colchicine group (OR 0.35, 95% CI 0.25-0.48, I2 0%) compared with controls. A subgroup analysis limited to hospitalized patients (OR 0.35, 95% CI 0.25-0.50, I2 0%) revealed similarly lower mortality in the colchicine group. Conclusions This meta-analysis suggests a mortality benefit with colchicine when used in the treatment of COVID-19 patients. The majority of included studies were observational; thus, the findings of this review need to be further supported by the results of ongoing trials. Other Information Published in: European Journal of Clinical Investigation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/eci.13645